Paralytic Shellﬁsh Poisoning due to ingestion of contaminated mussels: a case report in Caparica (Portugal) - Ribeiro, I. (2020)
In Portugal, the potent paralytic shellfish toxins (PSTs) have appeared irregularly since the onset of a national monitoring program for marine biotoxins in 1986. In years where high contamination levels were attained in bivalves, sporadic cases of human poisonings have been recorded, as in 1994 and 2007. The reappearance of high contamination levels led to the appearance of new cases during the autumn of 2018. This study reports the case of two patients that ingested mussels from the Portuguese southwest coast and required hospitalization due to the severity of symptoms. Details of toxin ingestion, symptomatology and toxin metabolization in the fluids are described. The diagnosis was confirmed by ELISA in plasma and urine samples. In mussel samples, the toxin profile obtained by HPLC-FLD displayed a wide diversity of toxins, typical of Gymnodinum catenatum ingestion. However, in the urine samples toxin profile was reduced to B1 and dcSTX. Abundant compounds in mussels having an O-sulfate at C11, such as C1+2 and dcGTX2+3, were absent in urine. In plasma, PSTs were not detected by HPLC-FLD. Calculated toxin ingestion, resulting from consumption of an estimated 200-gram portion, was in the range of 104-120 µg STX eq./kg b.w. This study alerts physicians to be aware of this human syndrome with only sporadic occurrence in Portugal.